2011
DOI: 10.1007/s00211-011-0400-5
|View full text |Cite
|
Sign up to set email alerts
|

A unification of unitary similarity transforms to compressed representations

Abstract: In this paper a new framework for transforming arbitrary matrices to compressed representations is presented. The framework provides a generic way of transforming a matrix via unitary similarity transformations to, e.g., Hessenberg, Hessenberg-like form and combinations of both. The new algorithms are deduced, based on the Q R-factorization of the original matrix. Relying on manipulations with rotations, all the algorithms consist of eliminating the correct set of rotations, resulting in a matrix obeying the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…It is worth noticing that the matrix C plays an important role for the design of fast structured variants of the QR iteration applied to perturbed Hermitian matrices. Specifically, in [4,20] it is shown that the sequence of perturbations C k : = Q H k C k−1 Q k yields a description of the upper rank structure of the matrices A k : = Q H k A k−1 Q k generated under the QR process applied to A 0 = A. The case where A = U + xy H is a rank-one correction of a unitary matrix U is particularly interesting for applications to polynomial root-finding.…”
Section: Almost Hermitian or Unitary Matricesmentioning
confidence: 99%
See 2 more Smart Citations
“…It is worth noticing that the matrix C plays an important role for the design of fast structured variants of the QR iteration applied to perturbed Hermitian matrices. Specifically, in [4,20] it is shown that the sequence of perturbations C k : = Q H k C k−1 Q k yields a description of the upper rank structure of the matrices A k : = Q H k A k−1 Q k generated under the QR process applied to A 0 = A. The case where A = U + xy H is a rank-one correction of a unitary matrix U is particularly interesting for applications to polynomial root-finding.…”
Section: Almost Hermitian or Unitary Matricesmentioning
confidence: 99%
“…It is worth noticing that the matrix C plays an important role for the design of fast structured variants of the QR iteration applied to perturbed Hermitian matrices. Specifically, in [4,20] it is shown that the sequence of perturbations…”
Section: Almost Hermitian or Unitary Matricesmentioning
confidence: 99%
See 1 more Smart Citation